P147 Safety of AbatacePt in Rheumatoid arthritis associated Interstitial Lung disease (APRIL). (26th April 2021) - Gudu, Tania; Stober, Carmel; Fifield, Maeve; Babar, Judith; Ostor, Andrew; Parfrey, Helen; Hall, Francess
Abstract: Background/Aims   Interstitial lung disease (ILD) is the commonest extra-articular complication of rheumatoid arthritis (RA) and is associated with a median survival of 3-8 years. Although biologic therapies are effective for synovitis, they can exacerbate the ILD. RA patients with significant ILD but minimal synovitis have limited therapeutic options. Case reports and retrospective analyses suggest that Abatacept may have efficacy in RA-ILD. However, use of potent immunosuppression in patients with chronic lung disease may increase the incidence of lower respiratory tract infection (LRTI). The purpose of this prospective study was to evaluate the safety of Abatacept in patients with progressive RA-ILD. Methods   This was a prospective, open-label, study of 19 RA patients (2010 ACR/EULAR criteria) with ILD. Patients were included if either serial thoracic computed tomography (CT) or pulmonary function tests (PFT) indicated progressive ILD over the preceding 14 months. Intravenous Abatacept was administered at baseline, 2, 4, 8, 12, 16 and 20 weeks. PFTs, thoracic CT scan and questionnaires were performed at baseline and week 20. The number of LRTI was recorded. Primary outcome: change in Forced Vital Capacity (FVC). Secondary outcomes: Transfer Factor (TLCOc), King's Brief Interstitial Lung Disease (K-BILD) Questionnaire, the Leicester Cough Questionnaire (LCQ) and radiological scores (percentage involvement of lung fields scored separately for ground-glass opacification, fibrosis, honeycombing and consolidation). Results   Preliminary data from the study are reported. Ten patients completed the study: 6 male, 6 ex-smokers, mean age 68±8.21 years, mean RA duration 6±5.4 years. The APRIL study was terminated due to safety concerns in the context of COVID-19 pandemic; nine patients were withdrawn for this reason. LRTI occurred in 4 patients (one patient had 2 LRTI). There were no serious adverse reactions. The mean FVC remained stable during the course of the study. There was a trend towards improvement in the LCQ and improvement in the K-BILD score. ILD-related changes on thoracic CT were stable in 9 of the patients. Conclusion   Our data indicates that abatacept has an acceptable safety profile in progressive pulmonary fibrosis associated with RA-ILD. This small dataset also suggests that ILD has not progressed during the period of treatment. Disclosure   T. Gudu: None. C. Stober: None. M. Fifield: None. J. Babar: None. A. Ostor: None. H. Parfrey: None. F. Hall: Grants/research support; FH has received a grant of £168k from Bristol Myers Squibb for the APRIL study.